The art of software testing - Myers, Glenford J., 1946- (John Wiley & Sons, 2004)
This long-awaited revision of a bestseller provides a practical discussion of the nature and aims of software testing. You'll find the latest methodologies for the design of effective test cases, including information on psychological and economic principles, managerial aspects, test tools, high-order testing, code inspections, and debugging. Accessible, comprehensive, and always practical, this edition provides the key information you need to test successfully, whether a novice or a working programmer. Buy your copy today and end up with fewer bugs tomorrow.